PATHOGENIC VARIABILITY AMONG THE ISOLATES OF FUSARIUM OXYSPORUM F. SP. LYCOPERSICI (FOL) CAUSING WILT OF TOMATO IN TELANGANA STATE - JAGADEESWAR. R; ANITHA KUMARI. D, KISHORE KUMAR. CH. S, BHARATI N. BHAT (The Journal of Research, PJTSAU, 2023)
Tomato is very often affected by several diseases incited by pathogens such as fungi, bacteria, viruses and nematodes. Among the fungal diseases, Fusarium wilt of tomato caused by Fusarium oxysporum f. sp. lycopersici (Fol), is one of the most destructive diseases across the world causing severe economic losses, wherever tomato is grown. Roving surveys were conducted in major tomato crop growing areas of Telangana state viz., Adilabad, Sangareddy and Rangareddy during the year 2017- 18. Fifteen isolates of Fusarium oxysporum f. sp. lycopersici collected from different tomato growing areas of Telangana were studied for their pathogenic variability and was observed that, Fol isolate collected from Adilabad district was found to be more virulent in causing disease incidence and disease severity when inoculated to susceptible tomato cv. Pusa Ruby compared to the other fourteen isolates collected from different places of Telangana. All the Fol isolates were found to be pathogenic by causing diseased wilt symptoms on cv. Pusa Ruby. Further, all the fifteen isolates were characterized at molecular level with species specific primer ITS 1(5’TCCGTAGGTGAACCTGCGG-32) and ITS 4 (5’-TCCTCCGCTTATTGATATGC-32 ) and by using ISSR primers which revealed the relationship among the fifteen isolates with varied degree of coefficient.